2011
DOI: 10.1210/jc.2010-1418
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Receptor for Advanced Glycation End Products System in Women with Severe Preeclampsia

Abstract: Fetal membranes are a rich source of sRAGE. Elevated maternal serum and amniotic fluid sRAGE and esRAGE, paralleled by increased RAGE expression in the amniochorion, suggest activation of this system in sPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…Here, we also found that the levels of sRAGE in umbilical cord blood were significantly decreased in women with sPE, and we did not detect any correlations between these levels and those of inflammatory cytokines. Another study reported that cord blood sRAGE levels were not affected by sPE, but the affected women had higher serum and amniotic fluid sRAGE and esRAGE levels than those expected for gestational age [34] . Therefore, the low level of sRAGE in umbilical cord blood might be associated with the activation of the AGE-RAGE system in the neonate and the oxidative stress or inflammatory responses in the maternal-fetal interface, or might be influenced by the higher levels in amniotic fluid, and unaffected by inflammation or PE.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Here, we also found that the levels of sRAGE in umbilical cord blood were significantly decreased in women with sPE, and we did not detect any correlations between these levels and those of inflammatory cytokines. Another study reported that cord blood sRAGE levels were not affected by sPE, but the affected women had higher serum and amniotic fluid sRAGE and esRAGE levels than those expected for gestational age [34] . Therefore, the low level of sRAGE in umbilical cord blood might be associated with the activation of the AGE-RAGE system in the neonate and the oxidative stress or inflammatory responses in the maternal-fetal interface, or might be influenced by the higher levels in amniotic fluid, and unaffected by inflammation or PE.…”
Section: Discussionmentioning
confidence: 95%
“…Increased levels of RAGE in women with PE have been shown in some [21] , but not all studies [22] . Compared with nonpregnant women, the sRAGE serum level was found reduced in pregnancy, but its course produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, AGEs are dramatically increased in some disorders; especially in those patients who suffer from oxidative stress with conditions such as diabetes, rheumatoid arthritis, systemic lupus erythematosus, Alzheimer's disease, or in cigarette smokers. Olier et al [9] have found that the expression of AGEs in maternal serum of patients with pre-eclampsia was significantly higher when compared to the expression in normal pregnant women and non-pregnant women. Gueds et al [10] have also shown that the accumulation of AGEs can cause oxidative stress in the placenta and placental vascular dysfunction, and thus lead to pre-eclampsia.…”
Section: Biological Activity Of Agesmentioning
confidence: 99%